Münchhausen-syndrom by proxy - Mogensen, Joan; Brun, Birgitte (Psyke & Logos, 2016)
Münchausen syndrome by proxy is a form of child abuse, characterized by a mother harming her child, either by making it ill or by producing false symptoms or stories intending to initiate medical examinations and treatment. In this article, focus is on the phenomenological description of the perpetrator, primarily based on experience and knowledge gathered through psychological assessment of these mothers in a Danish context. The phenomenological description challenges the dominating opinion concerning the basic psychopathology, which identifies the mother as suffering from a personality disorder. It is tentatively argued that at the core of their personalities these women are psychotic.